Understanding Spiritual Principles or Depending on Techniques To Realize and Sustain Optimal Mental Health. Issue 3 (2nd July 2016) - Kelley, Thomas; Pransky, Jack; Lambert, Eric
ABSTRACT: The primary goal of positive psychology is understanding and facilitating optimal mental health. However, absent fundamental causal principles that explain human psychological experience, positive psychology is unlikely to achieve this goal. We posit that fundamental causal principles may already have been uncovered, and we offer a study that tests the process from exposure to these principles to improved mental health. The results appear to support our prediction that insights regarding "thought recognition" and/or "innate mental health via a clear mind" gained through understanding these principles will show a significant positive relationship with hedonic well-being, eudaimonic well-being, social well-being, and optimal mental health. Of participants exposed to the understanding grounded in these spiritual principles, 88% were diagnosed as "flourishing."